TINDAK TUTUR DALAM PIDATO PRESIDEN JOKO WIDODO “VISI INDONESIA” (SPEECH ACTION IN PRESIDENT JOKO WIDODO'S SPEECH “VISION OF INDONESIAN”) - Dimas Fajar Ariyanto Putra (Universitas Lambung Mangkurat, 2023)
AbstractSpeech Actions in President Joko Widodo's Speech